2011
DOI: 10.1038/hr.2011.126
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive treatment using an angiotensin receptor blocker and a thiazide diuretic improves patients’ quality of life: The Saga Challenge Antihypertensive Study (S-CATS)

Abstract: The aim of the Saga Challenge Antihypertensive Study (S-CATS), a single-arm, prospective and multi-center trial, was to evaluate the effectiveness of combined antihypertensive treatment with losartan and hydrochlorothiazide (HCTZ). Enrolled in the study were a total of 161 patients with hypertension, who in spite of treatment with an angiotensin receptor blocker (ARB) alone or an ARB and calcium channel blocker (CCB), had not been able to reach blood pressure control goals set by the Japanese Society of Hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…* Our research design additionally minimizes the possible effect of other confounding factors as implemented medication. 49,50 Nevertheless, it could be useful to explore our hypothesis in multiple time points to establish more solid evidence.…”
Section: Discussionmentioning
confidence: 99%
“…* Our research design additionally minimizes the possible effect of other confounding factors as implemented medication. 49,50 Nevertheless, it could be useful to explore our hypothesis in multiple time points to establish more solid evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Advance Publication by-J-STAGE ies of combination drugs for HT showed improved adherence and patient QOL. 19, 20 Chen et al reported that the incidence of AEs ranged from 7.0% to 9.6% in patients receiving antihypertensive drugs, and that patients who had not experienced AEs had higher satisfaction. 21 In the present study, there were relatively low incidence rates for AEs (4.7%) and ADRs (2.4%).…”
Section: Safetymentioning
confidence: 99%
“…Previous reports have also shown that combination treatment with losartan/HCTZ safely and steadily reduces the BP (19)(20)(21) and improves the quality of life in patients with uncontrolled hypertension (21). Furthermore, in patients with symptomatic internal carotid artery or middle cerebral artery steno-occlusive disease, this drug regimen also safely lowers the BP without worsening the cerebral hemodynamics (22).…”
Section: Discussionmentioning
confidence: 99%